2020
DOI: 10.1002/anie.202005715
|View full text |Cite
|
Sign up to set email alerts
|

Organic‐Free Synthesis of Zeolite Y with High Si/Al Ratios: Combined Strategy of In Situ Hydroxyl Radical Assistance and Post‐Synthesis Treatment

Abstract: Zeolite Y, with a high SiO2/Al2O3 ratio (SAR), plays an important role in fluidized catalytic cracking processes. However, in situ synthesis of zeolite Y with high SARs remains a challenge because of kinetic limitations. Here, zeolite Y with an SAR of 6.35 is synthesized by a hydroxyl radical assisted route. Density‐functional theory (DFT) calculations suggest that hydroxyl radicals preferentially enhanced the formation of Si‐O‐Si bonds, thus leading to an increased SAR. To further increase the SAR, a dealumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 31 publications
(21 reference statements)
0
31
0
2
Order By: Relevance
“…13–18 Considerable efforts have been made to increase the SiO 2 /Al 2 O 3 ratio of zeolites and several strategies have been developed so far involving: (1) control of the SiO 2 /Al 2 O 3 ratio in the reaction mixture; 19–21 (2) dealumination of zeolites via post-treatment, including hydrothermal steaming and chemical leaching such as acids, salts, chelating agents, SiCl 4 or other halides and the combination of both the methods; 22–29 (3) use of organic structure-directing agents, especially those with a high C/N ratio or low charge density 16,17,30–34 and (4) introduction of hydroxyl radicals (·OH) or metal ions. 35,36 For example, an ultrastable Y zeolite (USY) widely used as a fluid catalytic cracking catalyst is usually prepared via the high-temperature hydrothermal steaming of NH 4 Y with a low SiO 2 /Al 2 O 3 ratio. 37 However, the post-treatment methodology has several drawbacks such as causing a significant decrease of the crystallinity of zeolites, requiring the NH 4 + or H + -form of zeolites achieved by multiple cycles of the ion-exchange process or involving corrosive chemicals such as SiCl 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13–18 Considerable efforts have been made to increase the SiO 2 /Al 2 O 3 ratio of zeolites and several strategies have been developed so far involving: (1) control of the SiO 2 /Al 2 O 3 ratio in the reaction mixture; 19–21 (2) dealumination of zeolites via post-treatment, including hydrothermal steaming and chemical leaching such as acids, salts, chelating agents, SiCl 4 or other halides and the combination of both the methods; 22–29 (3) use of organic structure-directing agents, especially those with a high C/N ratio or low charge density 16,17,30–34 and (4) introduction of hydroxyl radicals (·OH) or metal ions. 35,36 For example, an ultrastable Y zeolite (USY) widely used as a fluid catalytic cracking catalyst is usually prepared via the high-temperature hydrothermal steaming of NH 4 Y with a low SiO 2 /Al 2 O 3 ratio. 37 However, the post-treatment methodology has several drawbacks such as causing a significant decrease of the crystallinity of zeolites, requiring the NH 4 + or H + -form of zeolites achieved by multiple cycles of the ion-exchange process or involving corrosive chemicals such as SiCl 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that introducing ·OH radicals into the organic-free synthesis system of zeolite Y by adding H 2 O 2 can increase the SiO 2 /Al 2 O 3 ratio of zeolite Y from 5.78 to 6.35. 35,39 The density functional theory (DFT) calculations revealed that the increase of the SiO 2 /Al 2 O 3 ratio of zeolite Y is due to the facilitating effect of ·OH radicals on the formation of Si–O–Si bonds than Si–O–Al bonds. Very recently, it was reported that the introduction of Co 2 + during the synthesis can also increase the SiO 2 /Al 2 O 3 ratio of zeolite Y from 5.2 to 6.15.…”
Section: Introductionmentioning
confidence: 99%
“…Direct synthesis of high‐silica Y is undoubtedly the most attractive way. Typically, the SAR of zeolite Y from inorganic system is less than 6.5, [7] which has to require a subsequent dealumination to enhance the framework SAR in order to satisfy the requirements of industrial application. Utilizing organic structure‐directing agents (OSDAs) could help improve framework SAR, which has worked effectively for widening the compositions of zeolitic materials [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Table S1 gathers the state‐of‐the‐art synthesis protocols for high‐silica FAU. As seen, the Si/Al molar ratios in the final zeolite products can barely surpass 3 under organic‐free conditions (Entries 1 and 2, Table S1), even though great efforts have been made by carefully adjusting the synthesis parameters or by introducing hydroxyl radicals [18, 19] . This supposed limit is due to the decrease in the crystallization rate, or the increase in the apparent activation energy, when increasing the Si/Al ratio in the crystallization product [20] .…”
Section: Introductionmentioning
confidence: 99%